PENGARUH BRAND IMAGE DAN PERCEIVED QUALITY TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING (Studi Kasus pada Maskapai Penerbangan Garuda Indonesia) - Rahmatina, Missfala; Saryadi, Saryadi; Listyorini, Sari (Jurnal Ilmu Administrasi Bisnis, 2016)
The high mobility of people to move in a short time has brought a shift in the use of air transport services continues to increase passenger numbers from year to year. Garuda Indonesia is one of the service providers state-owned airline which also increased the number of passengers even if put up fares are relatively higher than other airlines. Business development in the field of rapid airline could not be separated from the ability of the airline Garuda Indonesia create a brand image, establish perceived quality, and achieve customer satisfaction, so as to create customer loyalty. In this research used purposive sampling techniques on 100 respondents passenger airline Garuda Indonesia. Data collection techniques and research instruments using a questionnaire. The data obtained were analyzed quantitatively using SPSS, through validity and reliability test. While data analysis is done through a simple linear regression analysis, multiple linear regression, t-test, F test and path analysis. Based on the analysis it is known that the influence of the variable path brand image and perceived quality variable to variable, namely customer loyalty, brand image variables have a direct impact at 0,113, and the perceived quality variables have a direct impact at 0.170. Consumer satisfaction as an intervening variable has an effect of 0.378 to variable customer loyalty. Then, if the brand image through customer satisfaction to influence customer loyalty, known to influence by 0.542. Meanwhile, if the perceived quality through customer satisfaction to influence customer loyalty, known to influence by 1.039. Based on this it can be seen that, the influence of brand image and perceived quality on customer loyalty will be greater if through customer satisfaction. Based on the test results of the variable F brand image, perceived quality and customer satisfaction to customer loyalty together look that F count> F table (18.916> 3.9391), and the results show that the brand image, perceived quality and customer satisfaction has a positive influence on customer loyalty. The conclusion from this study is the higher brand image, perceived quality and consumer satisfaction of Garuda Indonesia, the higher the customer loyalty. The advice given is so much improved quality of service provided by the service better and more diverse facilities.